PERBAIKAN KUALITAS LAYANAN DENGAN INTEGRASI SERQUEL, KANO, DAN QFD (Studi Kasus: Home Gym Palembang) - Fernando Theresia Sunarni (Jurnal Ilmiah Dinamika Teknik, 2018)
Home Gym Palembang is one service company that provides indoor sports facilities. Based on the results of interviews with 10 people found that 40% have complaints againts the services provided, 40% have complaints againts the facility such as beverage facilities, and the rest have complaints against the tools provided by the gym. Use of Service Quality, Kano, and Quality Function Deployment integration methods can help to improve service quality improvement. Based on Service Quality processing, it is found that customer satisfaction is not satisfied. The use of Kano method to help the gym know the attributes that need to get priority improvement where 5 service attributes in one-dimensional category, 3 service attributes in must-be category, and 8 service attribute in attractive category. The next step is integrated into the Quality Function Deployment to translate the customer’s and obtained as many as 16 pieces of technical response to service quality improvement. The average of the gap score before implementation is -1,393 (negative) and the average value of gap score after implementation is 0,176 (positive). The average decrease in gap score before and after the implementation of each service attribute to all service attributes of 3,226% which means the level of service quality at Home Gym increase. The results of the sign test between before and after implementation shows that there is a difference between before and after implementation with a significance value of 0,000 < 0,05. Keywords: Service Quality, Kano, Quality Function Deployment, Gym.